Causal Relationship Between Islamic Stocks and Staple Food Commodities of Largest Muslim on South-East Asian Countries - Dini Lestari; Sudarso Kaderi Wiryono (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
With many adherents of Islam, it is appropriate for the Muslim-dominant countries such as Indonesian and Malaysia capital markets to accommodate the investment needs of the community in line with sharia principles. Staple food commodity is one of the crucial commodities which can affect the mobility of stock prices. This paper examines the relationship between staple food commodities and Islamic capital markets. Using MGARCH and robustness VAR technique analysis and monthly data from 2017-2021, the empirical evidence suggests that getting information about the dynamic correlation between them is vital. The main findings from this study are that there are relationships among them in the long run and they have positive and negative correlations. From the point of view of investors with sharia compliance importance, it should be aware that staple food (rice) is more volatile rather than other staple food commodities (cooking oil) that will affect the Islamic Stocks Instrument.